2019
DOI: 10.1016/j.ymthe.2019.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Gene Therapy Using a Single Injection of Recombinant AAV9 Rescued SMA Phenotype in Mice

Abstract: Symptoms of spinal muscular atrophy (SMA) disease typically begin in the late prenatal or the early postnatal period of life. The intrauterine (IU) correction of gene expression, fetal gene therapy, could offer effective gene therapy approach for early onset diseases. Hence, the overall goal of this study was to investigate the efficacy of human survival motor neuron (hSMN) gene expression after IU delivery in SMA mouse embryos. First, we found that IU-intracerebroventricular (i.c.v.) injection of adeno-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Although these findings require validation in other mouse models of SMA, they extend our understanding of presymptomatic SMA. Our results suggest that effective delivery of therapy will likely require treatment in the presymptomatic phases of the disease, during the perinatal, or perhaps even prenatal, period in human patients ( 5 , 39 , 43 ). However, crucial ethical issues surround the use of human in utero gene therapy as a treatment strategy.…”
Section: Discussionmentioning
confidence: 94%
“…Although these findings require validation in other mouse models of SMA, they extend our understanding of presymptomatic SMA. Our results suggest that effective delivery of therapy will likely require treatment in the presymptomatic phases of the disease, during the perinatal, or perhaps even prenatal, period in human patients ( 5 , 39 , 43 ). However, crucial ethical issues surround the use of human in utero gene therapy as a treatment strategy.…”
Section: Discussionmentioning
confidence: 94%
“…For inherited genetic diseases, In-Utero Gene Therapy (IUGT) offers the potential of prophylaxis against early, irreversible, and lethal pathological change [ 413 ]. From a technical perspective, potential genetic therapeutic agents can be delivered to the fetus through infusion into the umbilical vein or via direct injection into the fetal organs.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…injection of a single-stranded or self-complementary AAV9-SMN vector extended their lifespan of 93 (median of 63) or 171 (median 105) days. Both muscle pathology and motor neuron survival improved upon treatments, with slightly better results from scAAV administration [ 413 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Similar to WS2A, which displays abnormalities of the retina as early as embryonic day 28 in pigs, there are several diseases that develop before birth and cause irreversible and fatal pathological change. In fetal mouse disease models, prenatal gene therapy has been exploited to prevent disease occurrence at the earliest stage as demonstrated by the treatment of hemophilia B, 67 acute neuronopathic Gaucher disease, 68 β-thalassaemia, 69 spinal muscular atrophy (SMA), 70 and hereditary tyrosinemia type 1, 55 indicating that prenatal gene editing is a promising approach for treating lethal diseases at the earliest stage. In the current study, we exploited the engineered BE (hA3A-eBE-Y130F) to correct the MITF c.740T>C mutation in SCNT-cloned embryos and demonstrated that efficient correction of this pathogenic mutation could be achieved through one-step microinjection of BE mRNA and sgRNA.…”
Section: Discussionmentioning
confidence: 99%